2020
DOI: 10.1177/0886260520905545
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Dating Violence Among College Student-Athletes

Abstract: College students are at increased risk for dating violence (DV) perpetration and victimization. One group of college students who may be at elevated risk is college student-athletes. While levels of athletic involvement range from National Collegiate Athletic Association (NCAA) Division I to Division III, there is currently a lack of information about the dating and relationship behaviors of male and female Division III student-athletes. This study identified the frequency of both minor and severe physical, ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 49 publications
4
21
1
1
Order By: Relevance
“…For student non-athletes, there was no statistical difference between feeling sad or not (16%) for the forced sexual intercourse (rape) outcome. Surprisingly, our results are inconsistent with prior work suggesting that student athletes represent a subgroup that is more susceptible to engaging in dating violence [ 27 , 28 ]. It is estimated that 19% of male student athletes account for all sexual violence cases reported to Judicial Affairs offices [ 29 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…For student non-athletes, there was no statistical difference between feeling sad or not (16%) for the forced sexual intercourse (rape) outcome. Surprisingly, our results are inconsistent with prior work suggesting that student athletes represent a subgroup that is more susceptible to engaging in dating violence [ 27 , 28 ]. It is estimated that 19% of male student athletes account for all sexual violence cases reported to Judicial Affairs offices [ 29 ].…”
Section: Discussioncontrasting
confidence: 99%
“…It is estimated that 19% of male student athletes account for all sexual violence cases reported to Judicial Affairs offices [ 29 ]. However, it is important to note that research on sexual violent behavior is limited and is highly controversial, with studies drawing different conclusions [ 27 ]. Therefore, our results should be cautiously interpreted given that additional thorough research will be needed to establish with more precision the risk factors differentiating student athletes and student non-athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Si bien se ha reportado que uno de cada cinco estudiantes secundarias mujeres reconocen haber sufrido abuso físico y/o sexual por parte de su pareja (APA, 2015), Cantor et al (2020) consideran que son los alumnos universitarios los que tienen mayor riesgo de perpetrar y padecer violencia en el noviazgo.…”
Section: Grupos De Discusiónunclassified
“…For instance, it has been shown that legitimating myths of IPV are linked to a certain reticence to accept IPV as a reality in some sectors of society, justification of the aggression, and victim responsibility (for example, previous insults, infidelity, going out without permission, etc. ), exoneration of the perpetrator, and to nonrecognition of IPV as such ( Taylor and Sorenson, 2005 ; European Commission, 2010 ; Giger et al, 2017 ; Cinquegrana et al, 2018 ; Lelaurain et al, 2018 , 2019 ; Cantor et al, 2021 ; Fakunmoju et al, 2021 ). These findings suggest that, to the extent that they endorse legitimating myths of IPV, the likelihood increases for women to legitimate and justify psychologically abusive behaviors.…”
Section: Introductionmentioning
confidence: 99%